Design of a Medication Reconciliation Application - Cadwallader, J.; Spry, K.; Morea, J.; Russ, A. L.; Duke, J.; Weiner, M. (Applied Clinical Informatics, 2013)
Background: Medication reconciliation is an essential, but resource-intensive process without a “gold standard” to measure medication adherence. Medication reconciliation applications that focus on facilitating clinicians’ decision-making are needed. Since no single available source of medication information is adequate, combining data sources may improve usefulness and outcomes.Objectives: We aimed to design a medication reconciliation application that could incorporate multiple data sources and convey information about patients’ adherence to prescribed medications. We discuss design decisions integral to developing medication reconciliation applications for the electronic health record. The discussion is relevant for health IT developers, clinical providers, administrators, policy makers, and patients. Three hypotheses drove our design of this application: 1) Medication information comes from a variety of sources, each having benefits and limitations; 2) improvements in patient safety can result from reducing the cognitive burden and time required to identify medication changes; 3) a well-designed user interface can facilitate clinicians’ understanding and clinical decision making.Methods: Relying on evidence about interface design and medication reconciliation, an application for the electronic health record at an academic medical center in the U.S. was designed. Multiple decisions that considered the availability, value, and display of the medication data are explored: Information from different sources; interval changes in medications; the sorting of information; and the user interface.Results: The prototype medication reconciliation application design reflects the visual organization, categorization, modality of interactions, and presentation of medication information from three data sources: patient, electronic health record, and pharmacy.Conclusions: A new medication reconciliation user interface displays information from multiple sources, indicates discrepancies among sources, displays information about adherence, and sorts the medication list in a useful display for clinical decision making. Gathering, verifying, and updating medication data are resource-intensive processes. The outcomes of integrating, interpreting, and presenting medication information from multiple sources remain to be studied.Citation: Cadwallader J, Spry K, Morea J, Russ AL, Duke J, WeineM. Design of a medication reconciliation application – facilitating clinician-focused decision making with data from multiple sources. Appl Clin Inf 2013; 4: 110–125http://dx.doi.org/10.4338/ACI-2012-12-RA-0057
Keywords: Medication reconciliation; decision making; computerized medical records systems; medication errors/prevention & control; user-computer interface